Multi -medium filter - LU SHAOFEI; XU GUIQIAN; WU XUEZHONG; ZHANG QIANG; LI XIAOFEI (2017)
The utility model relates to a water purifying and filtering equipment field, concretely relates to a to multi -medium filter. Including first casing, second casing, third casing, fourth casing, the 5th casing, first casing upper end is provided with the oral siphon, and the bottom of second casing is provided with first filter plate, and it has quartzy sand bed to pack on the first filter plate, and the bottom of third casing is provided with the second filter plate, and it has garnet layer in small, broken bits to pack on the second filter plate, and fourth casing bottom is provided with the third filter plate, and it has the resin layer to pack on the third filter plate, and the 5th casing lower extreme is provided with the outlet pipe. The utility model provides a multi -medium filter can effectively detach colloid, suspended solid and organic matter etc. Among the surface water and groundwater, has guaranteed good filter effect, and water after the filtration need not further purification, the reduction